Barometer Kepribadian Kepemimpinan Guru Agama Kristen di Era Disrupsi - Jannes Eduard Sirait (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2022)
The purpose of this study is to analyze, find and set a barometer of the leadership of Christian religious teachers in Indonesia. The main problem in the study: Christian religion teachers do not understand the barometer of Christian religion teachers' leadership and do not realize that they are leaders. There is a tendency that Christian religious teachers only understand themselves as teachers and educators. The next problem is that there is no specific theory regarding the barometer of Christian religious teacher leadership. So, the novelty of this research is the discovery and establishment of a new theory about the barometer of the leadership of Christian religious teachers in Indonesia. This research is a qualitative research that produces narrative data in the form of written words. Observations were made on the literature and other sources of information. The data collection method was observation and discussion with several Christian religious teachers. Then ask for responses from experts and compare them with the opinions of experts in the literature. Then do an in-depth analysis to find answers to research problems. The conclusion of the study is that the teacher leadership borometer includes: having the capacity to lead, being able to analyze situations, having authority, being able to control oneself, being humble, wise and chivalrous. Able to communicate, negotiate and have integrity.AbstrakTujuan penelitian ini adalah menganalisis, menemukan dan menetapkan barometer kepemimpinan guru agama Kristen di Indonesia. Masalah utama dalam penelitian: guru agama Kristen tidak mengerti barometer kepemimpinan guru agama Kristen dan tidak menyadari bahwa mereka adalah pemimpin. Kecenderungan yang ada bahwa guru agama Kristen hanya memahami dirinya sebagai guru dan pemberi pengajaran. Masalah berikutnya adalah belum ada teori secara khusus mengenai barometer kepemimpinan guru agama Kristen. Maka, kebaruan penelitian ini ialah ditemukan dan ditetapkannya suatu teori baru tentang barometer kepemimpinan guru agama Kristen di Indonesia. Penelitian ini merupakan penelitian kualitatif yang menghasilkan data naratif berupa kata-kata tertulis. Pengamatan dilakukan pada literatur dan sumber informasi lainnya. Metode pengumpulan data adalah observasi dan diskusi dengan beberapa guru agama Kristen. Kemudian meminta tanggapan dari para pakar dan membandingkannya dengan pendapat para pakar dalam literatur. Kemudian melakukan analisis mendalam hingga menemukan jawaban terhadap permasalahan penelitian. Kesimpulan penelitian bahwa bahwa borometer kepemimpinan guru mencakup: memiliki kapasitas memimpin, mampu meganalisa situasi, memiliki wibawa, mampu mengendalikan diri, rendah hati, bijaksana dan kesatria. Mampu berkomunikasi, melakukan negosiasi dan berintegritas.